(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
There are a lot of exposures to improve student’s speaking skill. Various learning methods and teaching techniques are implemented by teachers in order to achieve learning goal at the end of the semester for language students. One of them is presentation technique. The type of presentation discussed in this research is demonstrative presentation. This research aims at investigating how students can implement the demonstrative presentation in front of the class and finding out how the demonstrative presentation can influent the improving their ability in spoken English. The method used is descriptive analysis which is used to explain, analyze and classify something through various techniques, survey, interview, questionnaires, observations, and text. Students are assigned to design a demonstrative presentation using some theories explained before presentation session begins in the week four of the semester. The data are taken from the activity of English department students who take an Academic Presentation course in the 5th semester. The result shows that students present the demonstrative presentation personally by choosing a topic provided by the teacher. They present their topic accompanied by visual aids such as power point, poster or video to support their presentation. In addition, comments are given as feedbacks by the teacher for better presentation in the future. Student’s presentation is recorded and they are assigned to watch their own performance for better improvement as a self-reflection.